Pegylated Interferon-α–Induced Natural Killer Cell Activation Is Associated With Human Immunodeficiency Virus-1 DNA Decline in Antiretroviral Therapy–Treated HIV-1/Hepatitis C Virus–Coinfected Patients. (20th December 2017) - Hua, Stéphane; Vigano, Selena; Tse, Samantha; Zhengyu, Ouyang; Harrington, Sean; Negron, Jordi; Garcia-Broncano, Pilar; Marchetti, Giulia; Genebat, Miguel; Leal, Manuel; Resino, Salvador; Ruiz-Mateos, Ezequiel; et al.
Abstract : In antiretroviral-treated HIV-1/hepatitis C virus–coinfected patients, IFN-α treatment decreases cell-associated HIV-1 DNA levels, changes the natural killer (NK) cell subset distribution, and activates NK cells. Frequency and activation of NK cells are associated with lower cell-associated HIV-1 DNA. Abstract: Background: Interferon alpha (IFN-α) can potently reduce human immunodeficiency virus type 1 (HIV-1) replication in tissue culture and animal models, but may also modulate residual viral reservoirs that persist despite suppressive antiretroviral combination therapy. However, mechanisms leading to viral reservoir reduction during IFN-α treatment are unclear. Methods: We analyzed HIV-1 gag DNA levels in CD4 T cells by digital droplet polymerase chain reaction and CD8 T-cell and natural killer (NK) cell phenotypes by flow cytometry in a cohort of antiretroviral therapy–treated HIV-1/hepatitis C virus–coinfected patients (n = 67) undergoing treatment for hepatitis C infection with pegylated IFN-α and ribavirin for an average of 11 months. Results: We observed that IFN-α treatment induced a significant decrease in CD4 T-cell counts ( P < .0001), in CD4 T-cell–associated HIV-1 DNA copies ( P = .002) and in HIV-1 DNA copies per microliter of blood ( P < .0001) in our study patients. Notably, HIV-1 DNA levels were unrelated to HIV-1–specific CD8 T-cell responses. In contrast, proportions of total NK cells, CD56 bright CD16 – NK cells, and CD56 bright CD16 + NK cells were significantly correlated with reduced levels of CD4 T-cell–associated HIV-1 DNA during IFN-α treatment, especially when coexpressing the activation markers NKG2D and NKp30. Conclusions: These data suggest that the reduction of viral reservoir cells during treatment with IFN-α is primarily attributable to antiviral activities of NK cells.